Intracerebral inoculation of healthy non-transgenic rats with a single aliquot of oligomeric amyloid-β (1–42) profoundly and progressively alters brain function throughout life - Kramer, Marco; Hoang, Thu-Huong; Yang, Honghong; Shchyglo, Olena; Böge, Juliane; Neubacher, Ute; Colitti-Klausnitzer, Jens; Manahan-Vaughan, Denise (Frontiers in Aging Neuroscience, 2024)
One of the puzzling aspects of sporadic Alzheimer’s disease (AD) is how it commences. Changes in one key brain peptide, amyloid-beta (Aβ), accompany disease progression, but whether this comprises a trigger or a consequence of AD is still a topic of debate. It is clear however that the cerebral presence of oligomeric Aβ (1–42) is a key factor in early AD-pathogenesis. Furthermore, treatment of rodent brains with oligomeric Aβ (1–42) either in vitro or in vivo, acutely impairs hippocampal synaptic plasticity, creating a link between Aβ-pathology and learning impairments. Here, we show that a once-off inoculation of the brains of healthy adult rats with oligomeric Aβ (1–42) exerts debilitating effects on the long-term viability of the hippocampus, one of the primary targets of AD. Changes are progressive: months after treatment, synaptic plasticity, neuronal firing and spatial learning are impaired and expression of plasticity-related proteins are changed, in the absence of amyloid plaques. Early changes relate to activation of microglia, whereas later changes are associated with a reconstruction of astroglial morphology. These data suggest that a disruption of Aβ homeostasis may suffice to trigger an irreversible cascade, underlying progressive loss of hippocampal function, that parallels the early stages of AD.